AMPA Receptor Positive Allosteric Modulators: Potential for the Treatment of Neuropsychiatric and Neurological Disorders - Reuillon, Tristan; E. Ward, Simon; Beswick, Paul (Current Topics in Medicinal Chemistry, 2016)
The neurotransmitter glutamate and its receptors have long been of interest to scientists involved in pharmaceutical research since dysfunction of the glutamatergic signalling pathway has been associated with the pathophysiology of several psychiatric and neurological disorders. The research on AMPAR positive allosteric modulators offers opportunities to modulate fast excitatory synaptic transmission and identify new potential therapeutic agents for a range of neurodiseases. The field of AMPAR modulators continues to be a dynamic area of drug discovery with a pronounced diversification of the chemotypes explored in recent years. This article reviews literature published in this area in the last 6 years, focusing on the new core templates, some derived from high-throughput screens, with an emphasis on structure-activity relationships, drug metabolism and pharmacokinetics properties, and pharmacological profiles of these series.
Keywords: AMPAR positive modulators